Technical and Economic Indicators of Strategic Management Accounting in the Development Companies Based on the Life Cycle of the Produce - Akhmetzianov, Ainur A.; Sokolov, Andrew Y. (International Journal of Criminology and Sociology, 2022)
This article discusses the issues of technical and economic indicators of strategic management of a development company and the application of modern management accounting methods. We have analyzed various scientific studies of scientists in the field of product life cycle management and it was found that now this area is very popular and there is a demand for it from modern companies. In that reason for effective control and project planning, it has been proposed to use the Life Cycle Costing method, which can be successfully applied to development. This system was supplemented by the method of Target Costing, which is used for the target cost management. Using this method, the target price was determined, which was used to determine the acceptable margin of the development project at the planning stage. An interaction scheme of responsibility centers was proposed in order to achieve the implementation and effective operation of these systems, which allowed to reduce costs and accelerate sales. Using this proposal, it was possible to reduce design errors that led to significant additional costs.